Certifying Turkish Forests: A Path to Sustainable Forestry Practices - Durusoy, İdris; Türker, Mustafa Fehmi; Sıvacıoğlu, Ahmet; Akbulut, Sefa; Altunel, Arif Oğuz; Enez, Korhan; Sivrikaya, Fatih; Demirel, Döndü; Kara, Mehmet Erdal; Genç, Adem; Koç, Enüs; Şimga, Aslıhan; et al. (2023)
-